The Effects of MicroRNAs on Cardiomyopathy in a Rat Model of Streptozotocin-induced Diabetes Mellitus - Aslıhan Şeyda DOĞAN; Mukaddes PALA; Şenay GÖRÜCÜ YILMAZ; Ayfer BECEREN; Aydın KARABULUT; Yalçın POLAT; Hatice Kübra ELÇİOĞLU (Bezmiâlem Science)
Objective: Diabetic cardiomyopathy (DCM) is characterized by complex pathophysiological events. miRNAs play a role in the DCM. In our study, the potential of miRNAs as a biomarker in the diagnosis and treatment of DCM was evaluated in the diabetes model induced by streptozotocin in rats. Methods: Therefore, miRNAs obtained from rat heart tissue were analyzed by microarray, and twelve miRNAs (rno-miR-200c-3p, rno-miR-129-5p, rno-miR-150-3p, rno-miR-3584-5p, rno-miR-34c-3p, rno-miR-342-3p, rno-miR-466b-3p, rno-miR-466c-3p, rno-miR-31a-3p, rno-miR-15b-5p, rno-miR-196b-3p, and rno-miR-208a-5p) with changed expression levels were validated by real-time polymerase chain reaction analysis. Results: As a result of the validation, it was determined that three miRNAs (rno-miR-15b-5p, rno-miR-196b-3p, and rno-miR-208a-5p) were downregulated, one miRNA (rno-miR-200c-3p) was upregulated (p<0.05). MiR-15b-5p, miR-196b-3p, miR-200c-3p, and miR-15b-5p are involved in the regulation of DCM, and the GRAP2 gene is one of the possible targets of these miRNAs. Conclusion: miR-200c-3p has diagnostic value and may be a biomarker candidate.